Teachers’ Epistemological Stances and Citizenship Education (In Factis Pax: Journal of Peace Education and Social Justice, 2010)
This research explored differences among teachers’ epistemological and ontological world views and how their world views are related to their personal views on citizenship with respect to curriculum, pedagogy, and consistency over time. Several previous studies have examined changes in epistemological beliefs across time1 however, none of these studies examined change in both epistemological and ontological world views simultaneously, or whether changing world views are linked to changing beliefs about citizenship and citizenship education. We begin with a discussion of epistemological and ontological world views, and continue with an overview of citizenship education prior to presenting the results of the current study.